2003
DOI: 10.1194/jlr.r300011-jlr200
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of dietary supplements containing CLA for the treatment of obesity

Abstract: Dietary supplements containing conjugated linoleic acid (CLA) are widely promoted as weight loss agents available over the counter and via the Internet. In this review, we evaluate the efficacy and safety of CLA supplementation based on peer-reviewed published results from randomized, placebo-controlled, human intervention trials lasting more than 4 weeks. We also review findings from experimental studies in animals and studies performed in vitro. CLA appears to produce loss of fat mass and increase of lean ti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
107
0
11

Year Published

2006
2006
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 178 publications
(122 citation statements)
references
References 75 publications
(68 reference statements)
0
107
0
11
Order By: Relevance
“…25 We did not see a change in liver function tests including AST, ALT, ALP and total bilirubin. Of six recent studies including similar measures of liver function, only Gaullier et al 10,11 showed significant within-group increases in AST.…”
mentioning
confidence: 66%
See 2 more Smart Citations
“…25 We did not see a change in liver function tests including AST, ALT, ALP and total bilirubin. Of six recent studies including similar measures of liver function, only Gaullier et al 10,11 showed significant within-group increases in AST.…”
mentioning
confidence: 66%
“…Although some animal studies have shown negative effects with CLA, this is possibly attributable to greater doses: animals often receive 10-50 times the dosage per unit body weight compared to humans. 25 The effect of CLA on blood glucose and insulin sensitivity is controversial, Effect of CLA on body weight and composition AC Watras et al although reported deleterious effects appear to be primarily related to the trans-10, cis-12 CLA isomer. 6 Riserus et al…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although there is some evidence from mice and human studies that the CLA isomer trans-10, cis-12 may produce liver hypertrophy and insulin resistance via a redistribution of fat deposition that resembles lipodystrophy (Larsen et al, 2003), the CLA-induced changes in glucose tolerance and liver metabolism observed in the various animal studies are conflicting. For example, dietary CLA has been reported to decrease TG accumulation in the liver of Wistar rats (Purushotham et al, 2007), but hyperinsulinaemia was observed in wild-type mice supplemented with CLA (Tsuboyama-Kasaoka et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there is little information on how betaine and CLA affect serum hormone and metabolite profile. In addition, some deleterious effects have been reported when CLA was fed to laboratory animals, such as insulin resistance, liver enlargement and hepatic steatosis (Larsen et al, 2003). Thus, the effect of dietary CLA on liver function needs to be researched in non-rodent models.…”
Section: Introductionmentioning
confidence: 99%